The inner rhythm in the poetry of Izz al-Din al-Mawsili (d. 789 AH) - Fadel Karji, Randa; Khalaf Ruwaih, Balqees (Al-Adab Journal, 2020)
The poet Izz al-Din al-Mawsili is one of the prominent poets of the second Mamluk era, as the poet Izz al-Din was born in the eighth century AH, in the year (724 AH) and died in (789 AH) in Damascus. Ezz al-Din is an accomplished and eloquent poet. He is proficient in the systems. He has organized many poems and was the most creative in them, as he organized the muwashahat. He had the ability to organize puzzles, and he has many books. My research devoted this to the study of the internal rhythm of the poet’s studied hair, so I studied repetition, alliteration, and export.